Fortification of maternal milk - Cecilia Di Natale; Sandra Di Fabio (Hygeia Press di Corridori Marinella, 2013)
The beneficial effects of human milk (HM), well recognized for the term infant, extend to the feeding of premature infants, because their nutrition support must be designed to compensate for metabolic and gastrointestinal immaturity, immunologic compromise, and maternal psycosocial conditions. Studies show that preterm milk contains higher protein levels and more fat than term human milk. The American Academy of Pediatrics recommended that preterm neonates should receive sufficient nutrients to enable them to grow at a rate similar to that of fetuses of the same gestational age. There are no doubts about the fact that maternal milk is the best food for all neonates, but unfortified human breast milk may not meet the recommended nutritional needs of growing preterm infants. Human milk must therefore be supplemented (fortified) with the nutrients in short supply. The objective of fortification is to increase the concentration of nutrients to such levels that at the customary feeding volumes infants receive amounts of all nutrients that meet the requirements. The are two different forms of fortification of human milk: standard and individualized. The new concepts and recommendations for optimization of human milk fortification is the "individualized fortification". Actually, two methods have been proposed for individualization: the "targeted/tailored fortification" and the "adjustable fortification". In summary, the use of fortified human milk produces adequate growth in premature infants and satisfies the specific nutritional requirements of these infants. The use of individualized fortification is recommended.   Proceedings of the 9th International Workshop on Neonatology · Cagliari (Italy) · October 23rd-26th, 2013 · Learned lessons, changing practice and cutting-edge research